PENTINGNYA PENGGUNAAN PROGRAM APLIKASI INSTRUMENTASI DATA UNTUK MENGGALI ARAH PEMINATAN PESERTA DIDIK SMP DI KABUPATEN PAMEKASAN - Agus Supriadi (Jurnal Konseling Pendidikan Islam, 2021)
With so many tasks that must be completed cultivated fields by teachers Guidance and Counseling which consists of four fields, eleven types of services, and six support units. The teacher then Guidance and Counseling feel overwhelmed and unable to complete the task becomes all areas mandate, particularly in data collection and usage instrumentation applications. Unfinished inability to complete all the administrative tasks of the Guidance and Counseling teacher, now coupled with new task field known as Direction Specialisation, which according to teachers Guidance and Counseling " jobs that seem more time-consuming, and difficult to resolve in a short time ". So that guidance and counseling teacher performance was not optimal. In this research method is discussed about the development, stages, testing, and analysis products. To obtain the necessary data , the researchers chose 20 people teachers Guidance and Counseling are incorporated in MGBK (Musyawarah Guru Bimbingan dan Konseling ; Deliberation Teacher Guidance and counseling) Pamekasan as test subjects with treatment instrumentation applications utilizing the data direction of specialization. With this treatment were then given a questionnaire to determine the performance associated with speed and ease before and after using the instrumentation application of data toward specialization From the results of this development was obtained performance without using a program based on the pace of work = 38 : 80 = 0.475 or 47.5 % of the expected criteria. From the aspects of ease in working = 38 : 80 = 0.475 or 47.5 % of the expected criteria. While using the application program instrumentation toward specialization junior learners views on aspects of the system working speed = 66 : 80 = 0.825 or 82.5 % of that expected. Ease in working = 65 : 80 = 0.8125 or 81.25 % of the expected. For the lowest working system is the convenience aspect, which reached 81.25 % of the expected. From the calculation we can conclude the difference between a working system without and with using the program. So that the application program instrumentation specialization direction data can be harnessed and used by teachers Guidance and Counseling in Pamekasan to improve performance in the implementation of the service. Suggestions can be submitted to the user program the data instrumentation applications, especially towards specialization learners in making its recommendation sheet, to be able to properly and optimally utilize it possible to increase the performance of services to students of teaching.